Bioinspired Multistimuli‐Induced Synergistic Changes in Color and Shape of Hydrogel and Actuator Based on Fluorescent Microgels - Dongdong Lu; Qing Lian; Mingning Zhu (Advanced Science, 2024)
Abstract Fluorescent hydrogels have emerged as one of the most promising candidates for developing biomimetic materials and artificial intelligence owing to their unique fluorescence and responsive properties. However, it is still challenging to fabricate hydrogel that exhibits synergistic changes in fluorescence color and shape in response to multistimulus via a simple method. Herein, blue‐ and orange‐emitting fluorescent microgels (MGs) both are designed and synthesized with pH‐, thermal‐, and cationic‐sensitivity via one‐step polymerization, respectively. The two fluorescent MGs are incorporated into transparent doubly crosslinked microgel (DX MG) hydrogels with a preset ratio. The DX MG hydrogels can tune the fluorescent color accompanied by size variation via subjecting to external multistimulus. Thus, DX MG hydrogels can be exploited for multiresponsive fluorescent bilayer actuators. The actuators can undergo complex shape deformation and color changes. Inspired by natural organisms, an artificial morning glory with color and size changes are showcased in response to buffer solutions of different pH values. Besides, an intelligent skin hydrogel, imitating natural calotes versicolor, by assembling four layers of DX MG with different ratios of MGs, is tailored. This work serves as an inspiration for the design and fabrication of novel biomimetic smart materials with synergistic functions.